Răspunsuri

2014-04-01T18:43:05+03:00
A) -2x=4 - x=-2
b)2x-6=3x+6      
-x=12
c)4x+11+5x+20=2x+3
9x+22=2x+3         7x=21     rezulta x=3
d)7x+2-3x-1=6x+24-4x+3
4x+1=2x+27
2x=26-x=13
a) 3x-5x=6-2 , -2x= 4 imparit la (-2) ș x= -2
lucygagik ai gresit la calcule
2014-04-01T18:43:54+03:00
A)3x+2=5x+6
3x-5x=6-2
-2x=4 inmultim cu -1
x=-4/2=-2
b)2(x-3)=3(x+2)
2x-6=3x+6
2x-3x=6+6
-x=12        I-1
x=-12
c)4x+11+5(x+4)=2x+3
4x+11+5x+20=2x+3
9x+31=2x+3
9x-2x=3-31
7x=-28
x=-28/7=-4
d)7(x+2)-3x-1=6(x+4)-4x+3
7x+14-3x-1=6x+24-4x+3
4x+13=2x+27
4x-2x=27-13
2x=14
x=14/2=7